Root uptake of atenolol, sulfamethoxazole and carbamazepine, and their transformation in three soils and four plants - Kodešová, Radka; Klement, Aleš; Golovko, Oksana; Fér, Miroslav; Nikodem, Antonín; Kočárek, Martin; Grabic, Roman (Environmental science and pollution research international, 2019)
Soils can be contaminated by pharmaceuticals. The aim of this study was to evaluate the impact of soil conditions (influencing sorption and persistence of pharmaceuticals in soils) and plant type on the root uptake of selected pharmaceuticals and their transformation in plant-soil systems. Four plants (lamb's lettuce, spinach, arugula, radish) planted in 3 soils were irrigated for 20 days (26) with water contaminated by one of 3 pharmaceuticals (carbamazepine, atenolol, sulfamethoxazole) or their mixture. The concentrations of pharmaceuticals and their metabolites in soils and plant tissues were evaluated after the harvest. Sulfamethoxazole and atenolol dissipated rapidly from soils. The larger concentrations of both compounds and an atenolol metabolite were found in roots than in leaves. Sulfamethoxazole metabolites were below the limits of quantifications. Carbamazepine was stable in soils, easily uptaken, accumulated, and metabolized in plant leaves. The efficiency of radish and arugula (both family Brassicaceae) in metabolizing was very low contrary to the high and moderate efficiencies of lamb's lettuce and spinach, respectively. Compounds' transformations mostly masked the soil impact on their accumulation in plant tissues. The negative relationships were found between the carbamazepine sorption coefficients and its concentrations in roots of radish, lamb's lettuce, and spinach.
Keywords: listy rostlin; Plants; Carbamazepine; Soils; Raphanus; sulfamethoxazol; Sulfamethoxazole; atenolol; Metabolites; Plant-dependent compound’s transformation; látky znečišťující půdu; Atenolol; Soil; Soil Pollutants; rostliny; Compound’s translocation in plant; karbamazepin; Root uptake; Plant Leaves; Pharmaceuticals; půda